The Analysis of Spatial Distribution of Tourist Accommodation in Chiang Mai City - Sarnwong, Auttapan (สิ่งแวดล้อมสรรค์สร้างวินิจฉัย, 2025)
This study examines the spatial distribution patterns and factors influencing the density of three tourist accommodation types in Chiang Mai City: hotels, non-hotels (e.g., small accommodations such as hostels and guesthouses), and Airbnb rentals. Spatial distribution patterns were analyzed using Moran’s I index, while factors influencing accommodation density were evaluated through spatial regression analysis. The findings indicated significant clustering and overlap among all types of tourist accommodations within the city center, with hotels and non-hotels exhibiting particularly high concentrations. Airbnb rentals were more geographically dispersed across the city than hotels and non-hotels but still showed a notable concentration within the city center. Key factors influencing hotel density included proximity to popular tourist attractions and location within the old city area. In contrast, the density of Airbnb accommodation was more strongly associated with the presence of tourism-related services and facilities, such as shopping malls and cafes. These findings underscore the importance of integrating the distinct spatial patterns of various accommodation types into future planning and zoning policies. Such an approach is crucial for effectively regulating urban tourism expansion, mitigating the adverse impacts of overtourism, and preserving the local community’s well-being and quality of life.